Pertemuan Islam dan Kristen di Beranda Iman - Dadi Darmadi (Refleksi: Jurnal Kajian Agama dan Filsafat, 1998)
Broadly speaking, the book by Nicolas Jonathan Woly, derived from his doctoral dissertation, discusses the diverse opinions on interfaith relations from Islamic and Christian scholars and theologians in the 20th century. Woly does not seem to want to stop at such a typical discussion; rather, he also wants to specifically examine how such interreligious relationships influence the understanding of Christians and the church in their missiological tasks. Or, as he put it, "…The Church and Christians will listen and perhaps also learn from other religious communities in matters of its mission." In this regard, Woly explicitly states that Christians and the church should also receive input from their historical experiences of encountering people of other faiths.